Spreadsheet in everyday tasks of the Inspectorate of Education - Francisco de Pedro Sotelo (ADIDE Federación, 2008)
The scarce knowledge that inspectors of Education usually have of computer programs often make the use of word processors their only option, even in tasks for which these programs are unsuitable and may become a drawback to it rather than an advantage. In this article, we will focus on spreadsheet to help us out with the organization of our work, also as a checkpoint for visits to the schools we supervise and as control of official documents. We will develop it in a twenty-step process.